TUTOR'S ROLE IN PROFESSIONAL TRAINING OF THE POLICE OFFICERS - Alina Kudlay (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article analyzes the scientific literature, summarizes and systematizes pedagogically experience of the problem, reveals the essence and content of professional competence of future police officers, presents a functional and role-based view of communicative activities from the position of tutor, identifies the possibility of including a tutor tool in the formation of future communicative competence police officers. It is emphasized that tutor action is the most important emergent component of the holistic process of training future police officers, where the formation of communicative competence is an important task.